DIGITAL STORYTELLING: AN ACTIVE LEARNING TOOL FOR IMPROVING STUDENTS’ LANGUAGE SKILLS - Nassim, Shahala (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Storytelling method is an inevitable part of English Language classes. Stories are always an inspiring pedagogical tool to develop different language skills and to inculcate values and culture. In the present technological world, students lack the initiative to read stories and improve their reading skills. They lack interest in reading which has resulted poor reading and writing skills. Thus, a case study was done by integrating a technical tool to motivate students to read and improve their language skills and creativity. The study also aims to give a better understanding of the usage of multimodal approach like Digital storytelling in language learning classrooms. Microsoft photo story 3 was chosen to develop the stories into digital and 24 students of English Foundation level 2 were selected for the study. An evaluation rubric was developed to assess student’s digital story together with a survey to get students’ perception about the digital storytelling device in English classrooms. The study found the effectiveness of Digital story as a tool in enhancing their involvement in learning process and improving their reading, writing and creative skills. The findings of the study on Digital Story prove that it is a highly recommended tool for English Language students. Students enjoyed it as it demands technical and artistic involvement of the students. Students who participated in the study were engaged and improved their reading and writing skills by the end of the project. Throughout the process of story building, they developed how to organize, cooperate and collaborate to reach their goal. The tool can be implemented for blending learning purposes where the teachers or the students make their own contents and share to others.